FUEL SAVING AT METAL HEATING IN FURNACES OF MACHINE-BUILDING ENTERPRISES - A. A. Shipko; I. A. Trusova; I. N. Plushchevskij; S. V. Korneev; A. V. Tolstoj (Литьë и металлургия)
Economical efficiency of application of recuperative burners as compared to the modern traditional burners together with central recuperator and its system of control and automatic is shown.